Novel insight and perspectives of nanoparticle-mediated gene delivery and immune-modulating therapies for pancreatic cancer - Xinqiao Wang; Xue Yin; Yuxin Li; Shuhui Zhang; Meie Hu; Minjie Wei; Zhenhua Li (Journal of Nanobiotechnology)
Abstract Current standard-of-care therapies have failed to improve the survival of patients with metastatic pancreatic cancer (PCA). Therefore, exploring novel therapeutic approaches for cancer targeting is of utmost need. During the past few years, many efforts have been made to develop conventional treatment strategies to reduce chemotherapy resistance. However, critical challenges have impeded current cancer management outcomes, and limited clinical responses have been achieved due to unfavorable off-target effects. Advances in nanotechnology-based gene and immune-modulator delivery systems have excellent advantages for improving the therapeutic efficacy of PCA and provide promising avenues for overcoming the immunosuppressive tumor microenvironment and enhancing patient treatment outcomes. This review article provides insight into the challenges, opportunities, and future perspectives of these novel emerging nanoparticles based on lipid, polymer, and inorganic metal carriers to modulate genes and immunotherapy paradigms for PCA anticancer activity. Graphical Abstract